Firm Size as Moderation on Financial Performance, Capital Structure and Firm Value - Ahmad Salim; Oryza Milenia Kartika; Edy Suprianto (Jurnal Akuntansi Indonesia, 2026)
Abstract The purpose of this study is to determine the effect of financial performance and capital structure on firm value and the ability of firm size to moderate the relationship between financial performance and capital structure on firm value explained using Signaling Theory and Trade-Off Theory. The independent variables are financial performance and capital structure. The dependent variable is firm value. While the moderating variable is firm size. The population in this study is state-owned infrastructure sector companies listed on the IDX. The research sample uses purposive sampling with certain criteria, and the data that meets the criteria amount to 47 data. The data collection method uses the documentation method. While the data analysis technique uses SPSS Statistics 26 software. The results of this study are that financial performance does not affect firm value and capital structure has a negative effect on firm value. Firm size is unable to moderate the relationship between financial performance and firm value. However, firm size is able to moderate the relationship between capital structure and firm value.